THE DESIGN OF DISPLAY DIGITAL DATA INTERFACE CLAMP-METER COMPLEMENTED BY SENSOR GMR (GIANT MAGNETORESISTANCE) - Yulkifli Yulkifli; Fitri Afriani; Yohandri Yohandri; Ramli Ramli (Program Studi Fisika Universitas Negeri Jakarta, 2020)
This article discusses the design of a robust data interface system that displays an electric current using the GMR sensor. Robust measurement of electrical current to detect magnetic fields contained in the current-carrying wire. The magnetic field on the cable should be the input signal to the GMR sensor to be processed by the interface program. This interface used the Arduino IDE program and displayed in the LCD screen. This research is an experimental research laboratory. The results of the data interface can be displayed in the form of comparative measurements with the power of the conventional electric current. Comparison measurements can be viewed in graphical form. The results of the study have an average measurement accuracy of 91.2%, with an average of 0.96. Besides, this study also obtained a standard deviation of 0.21 and an average error of 0:08.